Estudo do perfil de aminoácidos salivares em crianças desnutridas com cárie da primeira infância - Costa, Dijane Pereira (2008)
Aim: The aim of the present study was to identify the free amino acid content in whole saliva of children with protein-energy malnutrition (PEM), with and without early childhood caries (ECC), correlating these findings with caries experience and mutans streptococci (MS) levels in saliva. Methods: One hundred and twenty two, 12 – 70 months-old children, with or without ECC were selected to participate in the study. Consent forms were signed and children were divided into healthy (GH, n = 47), and mildly (GI,n = 22) or moderately (GII,n = 53) malnourished groups. Malnourishment levels were classified according to WHO 2006 growth standards. Unstimulated whole saliva was collected from all participants and centrifuged. Supernatants were extracted, lyophilized, stored at – 20oC and used for amino acid analysis, on a Biochem 20 plus amino acid analyzer. Stimulated whole saliva was also collected from all subjects, and used for MS detection on MSB agar medium (cfu/mL). Amino acid concentrations were expressed in µM/mL. Dental examination was performed for calculation of dmfs scores. Pearson Chi-Square test and a Logistic Binary Model were used for statistical analysis. Results were considered significant when p-value < 0.02. Results: Forty amino acids were identified, with great variability in their concentrations. Analysis of presence/absence of each amino acid and presence/absence of caries demonstrated an association between asparagine and ECC in GII (p = 0.003). Logistic regression showed that caries experience increased with an increase in age (p = 0.003). The presence of alanine (p = 0.014) and carnithine (p = 0.008) reduced the chances of experiencing ECC. The presence of histidine significantly increased caries risk (p = 0.012). However, MS counts did not significantly increase the risk of experiencing ECC (p = 0.065) in this model. Conclusion: Presence of specific amino acids in saliva of children with PEM predisposes to a higher or lower risk of caries experience.